Extraoral Halitosis and Systemic Diseases: A Narrative Review - Edria Benita Tampubolon; Leonardo Jaya Setiadi Tanumiharja; Anna Nur Azizah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Introduction: Halitosis is a common condition characterized by an unpleasant odor originating from the oral cavity or extra-oral sources. While most cases are associated with intraoral factors such as tongue coating, periodontal disease, and poor oral hygiene, approximately 10–20% of halitosis cases are linked to extra-oral or systemic conditions. Methods: This study was conducted as a narrative review to provide an overview of the current understanding of halitosis, including its etiology, pathophysiology, diagnosis, and management, with particular emphasis on associated systemic diseases. Relevant literature was identified through searches of electronic databases including PubMed, Scopus, Web of Science, and Google Scholar. Result and Discussion: Extra-oral halitosis can be classified into non-blood-borne and blood-borne forms. Non-blood-borne halitosis arises from disorders of the respiratory tract, gastrointestinal system, and ear–nose–throat (ENT) region, whereas blood-borne halitosis results from volatile compounds entering the bloodstream and being exhaled through the lungs.Conclusion: Effective patient care often requires collaboration between dental practitioners and medical specialists. Recognizing halitosis as a potential manifestation of systemic disease enables earlier diagnosis, appropriate referral, and improved patient outcomes. Therefore, dental professionals play an important role in the multidisciplinary detection and management of halitosis associated with systemic disorders